Technology for Treating Oily Wastewater Derived from Various Industries: A Review Paper - Sri Martini; Mira Setiawati (CHEMICA: Jurnal Teknik Kimia, 2020)
The increasing number of industrial sectors has resulted in more and more contaminated water and wastewater containing various harmful pollutants including oil compounds. Less treated or untreated oily wastewater could give a serious threat to both human health and environmental sustainability. Therefore, the appropriate treatment methods such as membrane filtration, coagulation/flocculation, biological treatment, adsorption, and relevant integrated methods have to be implemented well to enhance the quality of those wastewaters before they flow into the final disposal place. This effort will endorse the success of waste management and circular economy system by recycling unwanted industrial by-products including wastewater, so it can be reused for further productive purposes.